State‐Level School Competitive Food and Beverage Laws Are Associated With Children's Weight Status1. (September 2014) - Hennessy, Erin; Oh, April; Agurs‐Collins, Tanya; Chriqui, Jamie F.; Mâsse, Louise C.; Moser, Richard P.; Perna, Frank
ABSTRACT BACKGROUND This study attempted to determine whether state laws regulating low nutrient, high energy‐dense foods and beverages sold outside of the reimbursable school meals program (referred to as "competitive foods") are associated with children's weight status. METHODS We use the Classification of Laws Associated with School Students (CLASS) database of state codified law(s) relevant to school nutrition. States were classified as having strong, weak, or no competitive food laws in 2005 based on strength and comprehensiveness. Parent‐reported height and weight along with demographic, behavioral, family, and household characteristics were obtained from the 2007 National Survey of Children's Health. Bivariate and logistic regression analyses estimated the association between states' competitive food laws and children's overweight and obesity status (body mass index [BMI]‐for‐age ≥85th percentile). Children (N = 16, 271) between the ages of 11‐14 years with a BMI for age ≥5th percentile who attended public school were included. RESULTS Children living in states with weak competitive food laws for middle schools had over a 20% higher odds of being overweight or obese than children living in states with either no or strong school competitive food laws. CONCLUSION State‐level school competitive food and beverage laws merit attention with efforts to address the childhood obesity epidemic. Attention to the specificity and requirements of these laws should also be considered.